How to prioritize species recovery after a megafire. Issue 5 (15th August 2022) - Ward, Michelle; Carwardine, Josie; Watson, James E. M.; Pintor, Anna; Stuart, Stephanie; Possingham, Hugh P.; Rhodes, Jonathan R.; Carey, Alexander R.; Auerbach, Nancy; Reside, April; Yong, Chuan Ji; Tulloch, Ayesha I. T.
Abstract: Due to climate change, megafires are increasingly common and have sudden, extensive impacts on many species over vast areas, leaving decision makers uncertain about how best to prioritize recovery. We devised a decision‐support framework to prioritize conservation actions to improve species outcomes immediately after a megafire. Complementary locations are selected to extend recovery actions across all fire‐affected species' habitats. We applied our method to areas burned in the 2019−2020 Australian megafires and assessed its conservation advantages by comparing our results with outcomes of a site‐richness approach (i.e., identifying areas that cost‐effectively recover the most species in any one location). We found that 290 threatened species were likely severely affected and will require immediate conservation action to prevent population declines and possible extirpation. We identified 179 subregions, mostly in southeastern Australia, that are key locations to extend actions that benefit multiple species. Cost savings were over AU300 million to reduce 95% of threats across all species. Our complementarity‐based prioritization also spread postfire management actions across a wider proportion of the study area compared with the site‐richness method (43% vs. 37% of the landscape managed, respectively) and put more of each species' range under management (average 90% vs. 79% of every species' habitat managed). In addition to wildfire response, our framework can be used to prioritize conservation actions that will best mitigate threats affecting species following other extreme environmental events (e.g., floods and drought). Resumen: Debido al cambio climático, los mega incendios son cada vez más comunes y tienen un impacto repentino y extenso sobre muchas especies en inmensas superficies, lo que deja a los tomadores de decisiones con incertidumbre sobre cuál es la mejor manera de priorizar la recuperación. Diseñamos un marco de apoyo a las decisiones para priorizar las acciones de conservación para mejorar los resultados para las especies inmediatamente después de un mega incendio. Para esto, se seleccionan localidades complementarias para extender las acciones de recuperación por todos los hábitats de las especies afectadas por el incendio. Aplicamos nuestro método a las áreas afectadas por los mega incendios de 2019–2020 en Australia y analizamos las ventajas de conservación del método mediante la comparación entre nuestros resultados y aquellos de un enfoque en la riqueza de especies (es decir, la identificación de las áreas que recuperan de manera rentable la mayor cantidad de especies en cualquier localidad única). Encontramos que 290 especies amenazadas estuvieron probablemente afectadas de manera severa y requerirán acciones inmediatas de conservación para prevenir la declinación poblacional y la posible eliminación. Identificamos 179 subregiones, la mayoría en el sureste de Australia, que son localidades clave para extender las acciones que benefician a muchas especies. El ahorro en los gastos fue de más de AU300 millones para reducir el 95% de las amenazas para todas las especies. Nuestra priorización basada en la complementariedad también extendió las acciones de manejo posterior al incendio a una mayor proporción del área de estudio en comparación con el método de riqueza de especies (43% versus 37% del paisaje gestionado, respectivamente) y colocó más de la distribución de cada especie bajo manejo (en promedio 90% versus 79% del hábitat manejado de cada especie). Además de la respuesta a los incendios, nuestro marco puede usarse para priorizar las acciones de conservación que mitiguen de mejor manera las amenazas que afectan a las especies después de otros eventos ambientales extremos (p. ej., inundaciones y sequía). 【摘要】: 由于气候变化, 特大火灾变得越来越常见, 且对广大地区的许多物种产生突然的、广泛的影响, 这导致决策者难以确定最佳的优先恢复次序。本研究设计了一个决策支持框架来对保护行动进行优先排序, 以改善大火发生后对物种的影响。我们提出, 选择互补的地点可以将恢复行动扩展到所有受火灾影响物种的栖息地之中。我们将该方法应用于2019‐2020年澳大利亚发生大火的地区, 并通过比较我们的结果与位点丰富度方法(即在一个地点确定高成本效益地恢复最多物种的地区)的结果, 评估了其保护优势。我们发现, 有290个受威胁物种可能受到严重影响, 需要立即采取保护行动, 以防止种群减少或灭绝。我们还确定了179个主要在澳大利亚东南部的亚区域, 作为扩大行动以帮助多个物种恢复的关键地点。我们的结果可以在减少所有物种中95%的威胁的情况下, 节约超过3亿澳元的成本。与位点丰富度方法相比, 我们基于互补性优先排序的方法还在研究区域的更大范围推广了火后管理行动(分别为受管理景观的43%和37%), 管理范围更多地覆盖了每个物种的分布范围(每个物种受管理的栖息地分别为平均90%和79%)。除了应对野火之外, 我们的框架还可以用于在其他极端环境事件(如洪水和干旱)中确定保护行动的优先次序, 以最好地减缓对物种的威胁。【翻译:胡怡思;审校:聂永刚】